Peran Inteligensi dalam Proses Belajar Mengajar - Habsy, Bakhrudin All; Febriani, Dwita; Posopati, Anggita Nawangwulan; Fitria, Verda (TSAQOFAH, 2024)
Intelligence is a way of thinking in solving a problem or directing an action. In general, students who have high intelligence will boast in class because they know which intelligence is suitable for the learning process, so that students will easily success. The purpose of this research is to find out how the role of intelligence in the learning process takes place in schools. The methods used in this research are qualitative methods using library studies as well as literature studies. The result is that intelligence plays an important role in learning, namely as a form of process in increasing the potential of learners in learning. To increase the potential of the student, educators must develop the learning process creatively.